2014
DOI: 10.1097/rli.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Contrast-Enhanced Spectral Mammography Compared With Full-Field Digital Mammography

Abstract: Compared with our institutional FFDM, the AGD of a single CESM exposure is increased by 1.25 mGy (+81%), whereas ESAK is increased by 3.07 mGy (+41%). Dose values of both techniques meet the recommendations for maximum dose in mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 17 publications
2
47
0
2
Order By: Relevance
“…Nevertheless, CESM cannot substitute MRI in all indications especially in patients with high‐risk of breast cancer (BRCA 1 and 2 carriers), for whom radiation exposure must be limited. Few studies have been published about the extra radiation dose induced by CESM . Fallenberg et al found only 6.2% increase in average glandular dose for CESM compared to MG .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, CESM cannot substitute MRI in all indications especially in patients with high‐risk of breast cancer (BRCA 1 and 2 carriers), for whom radiation exposure must be limited. Few studies have been published about the extra radiation dose induced by CESM . Fallenberg et al found only 6.2% increase in average glandular dose for CESM compared to MG .…”
Section: Discussionmentioning
confidence: 99%
“…Fallenberg et al found only 6.2% increase in average glandular dose for CESM compared to MG . In a study by Jeukens et al, dose values of both techniques met the recommendations for maximum dose in MG . Francescone et al demonstrated that low‐energy CESM images are equivalent to standard MG, and suggested that low‐energy CESM images may be used for interpretation in place of the MG, thereby reducing patient dose .…”
Section: Discussionmentioning
confidence: 99%
“…The average glandular dose (AGD) for a CESM has been reported as between 1.2–1.8 times that of a standard full FFDM and well within the accepted international dose limits for mammography . Fallenburg et al .…”
mentioning
confidence: 53%
“…In particular, considering the life attributable risk associated with an AGD value of 1.49 to 1.62 mGy, which is approximately 0.2 cases per 100,000 women aged 40 years, the difference is clinically negligible. 22 Importantly, for all acquisitions, the AGD was below the acceptable limits reported by the European Reference Organization for Quality Assured Breast Screening and Diagnostic Services guidelines. 20,23 Previous studies performed on Hologic Selenia Dimensions DBT systems have published dosimetric patient data for DBT ranging from 1.74 mGy (n = 179) to 2.56 mGy (n = 300), 14-17 which were higher than in the present study (1.49 [0.36] mGy).…”
Section: Discussionmentioning
confidence: 98%